JuxtaLearn taxonomy: a tool to help teachers to identify and understand the causes of student misunderstandings - Cruz, Sara (2018)
Threshold concepts are key concepts, often troublesome and complex, that are vital to understanding a subject. Once understood, threshold concepts have been described as akin to a portal, opening up new and previously inaccessible way of thinking about the subject. This paper presents an exploratory study that explored the use of a digital tool entitled „Juxta Learn taxonomy‟. This tool was designed to support teachers in identifying threshold concepts their students have problems in overcoming and for what reason they have problems understanding these concepts. We interviewed math and physical chemistry teachers, and based on „JuxtaLearntaxonomy‟ these teachers identified threshold concepts grounded on pedagogical practice, and the reason for their students have problems understanding these concepts. Results show that the taxonomy helped the teachers to identify threshold concepts and to break them down into smaller stumbling blocks illustrated by examples of student problems. So, we conclude that the tool allows teachers to reflect on the causes of these student misunderstandings and to think about appropriate pedagogical strategies to help the students overcome them.